Tindak Tutur Direktif Guru dalam Pembelajaran Bahasa Indonesia di SMP: Kajian Pragmatik - Rahmadhani, Dwi Putri; Hafizah, Farjul; Amelia, Putri; Putri, Hanifa (Paedagogie, 2026)
This study aims to find, describe, and analyze the forms and functions of directive speech acts used by teachers in the Indonesian language learning process at SMP Negeri 4 Bukittinggi. This type of research is qualitative research with descriptive methods. The research data are in the form of teacher and student speech during learning activities, which are obtained through the technique of free listening and conversation (SBLC), recording, and taking notes. The results of the study indicate that there are five types of directive speech acts used by teachers, namely (1) ordering or commanding, (2) requesting, (3) demanding, (4) suggesting, and (5) challenging. Of the five types, ordering or commanding speech acts are the most dominant form used, which is around 60-65% of the total data, while the challenging type is the least used form, around 5%. The dominance of the command form shows that teachers play an important role in directing and controlling the learning process. In addition, the use of other directive forms helps create an active, communicative, polite, and meaningful classroom atmosphere. These findings demonstrate that teachers are able to balance authority and politeness, enabling directive speech acts to play a crucial role in building effective educational communication and supporting the success of the teaching and learning process.